TBG-136, a Schizophyllum commune-derived β-glucan benefits gut microbiota and intestinal health: A randomized, double-blind, and placebo-controlled clinical trial - Hui-Yeon Jang; Su-Jin Jung; Eun-Ock Park; Soo-Dong Kim; Je-Kyoung Kim; Soo-Wan Chae; Youn–Soo Cha; Seung-Ok Lee (Journal of Functional Foods, 2023)
β-glucan exerts beneficial biological activities such as immunoregulatory, anticancer, antioxidative, antiaging, and wound healing. However, the effects of β-glucan on constipation have not been thoroughly studied. Thus, the present study aimed to investigate the effects of β-glucan-derived from Schizophyllum commune supplementation (TBG-136) on gut microbiota and intestinal health in constipated subjects. As a result, Lactobacillus was significantly increased in the TBG-136 group compared to the placebo group (P < 0.05) after 8 weeks of TBG-136 supplementation. Additionally, TBG-136 group significantly improved the rectosigmoid CTT and the number of defecations compared to the placebo group (P < 0.05). Thus, β-glucan derived from Schizophyllum commune helps individuals' health and quality of life by increasing the beneficial bacteria and improving symptoms of constipation.